A national survey of paediatric long-term ventilation in the UK. (29th September 2015) - Wallis, C; Jardine, E; Beaton, S; Paton, J
Abstract : Aims: The last decade has seen a significant increase in the number of children receiving long-term ventilatory (LTV) support. There are a number of reasons for this including improved home ventilators for children, better designed paediatric face masks and a new ethos for long-term respiratory support at home. A previous survey undertaken in 1997 revealed 136 such children. The current number and status are required for allocation of healthcare resources for these high-cost, complex children. Methods: Because of the protean nature of this cohort, it was elected to do a spot census. A standard questionnaire was devised by consensus and 39 lead clinicians were identified who supervise children on LTV in the UK. All children (<17 years) receiving ventilatory support for all/part of the 24-h day for a period of at least 3 months at midnight on the 30th September 2008 were included. Data were entered to an online form and after anonymisation and encryption were stored at a central data monitoring centre. Results: 944 children/young people were identified. 58% were male and 91% lived at home. 212 children were ventilated by tracheostomy while 714 used facial mask interface. Three children had phrenic nerve pacing in addition to a tracheostomy. 18 were unknown. The medical causes for ventilatory support were divided into three main categories: Respiratory: (350) of which upper airway obstruction and obesity dominated; 11 had chronic lung disease of prematurity; CNS: (184) of which 57 had congenital central hypoventilation, 22 had high spinal injury; 21 acquired hypoventilation; Musculoskeletal: (410) the commonest cause was Duchenne muscular dystrophy (92); 64 children had spinal muscular atrophy (SMA) type II and 12 SMA type I. Conclusions: This study has shown a very substantial increase in the numbers of children on LTV since the last UK survey. The increased use of non-invasive ventilation in neuromuscular patients is the main contributor. The vast majority of the children (including those on 24-h tracheostomy ventilation) are managed at home. These data will inform future health provision and also form the basis for a wider study into other aspect of home ventilation in childhood.